(untitled) (Polis (Santiago), 2018)
This article presents arguments in favor of designing public policies sensitive to multicultural challenge, especially taking into account that culture is a crucial element for individual identity. First, it reviews the dispute between liberals and communitarians as the source of the current debate. Second, it analyzes the Rawls’s response to communitarian critique. Third, it exposes critically the three most important model-conceptions that pronounce about cultural pluralism. And finally, it outlines a possible response to the demands of ethnic minorities.